PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP AUDIT DELAY DAN TIMELINESS - Yulintang Kurniawan; Herry Laksito (Diponegoro Journal of Accounting, 2015)
The purpose of this study was to examine the influence of Internal and External Factors on the likelihood of audit delay and timeliness . Indicators used to measure for internal company effect is profitability, solvency, company age, company size then external company effect is going concern audit opinion, audit delay is intervening variable and dependent variable is timeliness. This study uses secondary data to the entire population of companies listed in Indonesia Stock Exchange ( IDX ) 2012-2013. The method used to determine the sample using purposive sampling.Results of hypothesis testing showed that the size commpany, going concern audit opinion and age company have no significant effect on the likelihood of audit delay. While the proportion of independent profitability, reputation public accounting firm, solvency significantly affect the likelihood of audit delay and audit delay significantly affect the likelihood of timeliness.